DETERMINANTS OF COMPLIANCE WITH ACCESS TO GOVERNMENT PROCUREMENT OPPORTUNITIES REGULATIONS FOR SPECIAL GROUPS AMONG PARASTATALS IN KENYA - Oyugi, Abednego Momanyi; Getuno, Dr. Pamela (International Journal of Supply Chain and Logistics, 2019)
Purpose: The specific objectives of the study were; to assess the effect of prequalification criteria, opportunity awareness and sensitization, capacity of special groups and internal compliance controls on compliance with AGPO regulations for special groups among parastatals in Kenya. Methodology: The study employed a descriptive research design, targeting heads of procurement among parastatals of Kenya. The study preferred this method because it allows an in-depth study of the subject. Data was collected using self-administered questionnaires. The data collected was analyzed by use of descriptive and inferential statistics. Multiple regression models were used to show the relationship between the dependent variable and the independent variables. The data generated was keyed in and analyzed by use of Statistical Package of Social Sciences (SPSS) version 24 to generate information which was presented using charts, frequencies and percentages. Results: The F critical at 5% level of significance was 26.5. Since F calculated which can be noted from the ANOVA table above is 81.8 which is greater than the F critical (value= 26.5), this shows that the overall model was significant. The study therefore establishes that; prequalification criteria, opportunity awareness and sensitization, capacity of special groups, internal compliance controls affect compliance with AGPO regulations Conclusion: The findings of the study indicated that prequalification criteria, opportunity awareness and sensitization, capacity of special groups and internal compliance controls have a positive relationship with compliance with AGPO regulations for special groups among parastatals in Kenya Contribution to theory, practice and policy: The study recommended that public institutions should embrace prequalification criteria, opportunity awareness and sensitization, capacity of special groups and internal compliance controls so as to improve compliance with AGPO regulations for special groups.